Blind source separation using higher-order statistics - Ziauddin Muhammed Kamran. (2008)
In this thesis, we focus on the signal processing foundations of this emerging field of fundamental research with a broad range of applications. Specifically, we develop blind algorithms for estimating a set of signals of which only instantaneous linear mixtures are observed.